Restructing Eastern Germany - Lentz, Sebastian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
This yearbook of urban and regional studies provides English language papers on spatial development research on Germany and Central and Eastern Europe for researchers and practioners outside Germany.
Preface $1 (BIntroduction -- Perspectives and Options for Economic Policy in Eastern Germany $1 (BWith Special Reference to Aspects from the Spatial Sciences -- On the Difficulties involved with the Examination of Complex Policy Agendas -- Regional Disparities in the GDR $1 (BDo They Still Matter? -- Equal Living Conditions and their Fiscal Bases -- Interregional Support Policy for East German Regions -- New Spatial Patterns of Population Development as a Factor in Restructuring Eastern Germany -- Strengthening the Human Resource Base in Eastern German Regions -- Strategies for Urban Regeneration $1 (BThe Transformation of Cities in Northern England and Eastern Germany -- Urban Development with Olympic Games and World Exhibitions $1 (Bis it Possible to Plan Usage? -- Countries Undergoing Transformation $1 (3z(BNew(3y (BEuropean Neighbours in Spatial Planning -- Spatial Development Strategies in the New EU Member States: ESPON Project 2.2.2 on Pre-Accession Aid Impact Assessment -- The Knowledge Society and Spatial Development.s
Keywords: Geography; Regional planning; Urban planning; Civil engineering; Geography; Landscape/Regional and Urban Planning; Civil Engineering; Electronic books